CoQ10 alleviates hepatic ischemia reperfusion injury via inhibiting NLRP3 activity and promoting Tregs infiltration. (March 2023) - Zhang, Shaopeng; Gan, Xiaojie; Gao, Ji; Duan, Jie; Gu, Aidong; Chen, Changhao
Abstract: Hepatic ischemia-reperfusion injury (IRI) has been concerned as a main complication of liver surgery and transplantation. Previous studies show that reactive oxygen species (ROS) associated inflammation response and contribute to the liver damage during IRI. Coenzyme Q10 (CoQ10) has shown many beneficial effects on abrogating ROS production and ameliorating liver injury. This study found lower CoQ10 level in the process of liver IRI in a mouse model of hepatic IRI. Meanwhile, our results showed that CoQ10 administration significantly attenuate hepatic IRI proved by HE staining, serum ALT/AST. The NOD-like receptor protein 3 (NLRP3) inflammasome is activated by ROS which triggers the activation of inﬂammatory caspases. In this study, NLRP3 was significantly suppressed by CoQ10 while Foxp3 exhibited increased expression in liver. Furthermore, Kupffer cells (KCs) pretreated with CoQ10 under the condition of hypoxia and reoxygenation contributed to improved CD4 + CD25 + Foxp3 + regulatory T cells (Tregs) ratio in co-culture system. Furthermore, NLRP3 inflammasome activator treatment in vivo resulted in higher expression of caspase-1 and NLRP3 and reduction of Tregs in liver, which reversed the protection of CoQ10 in the liver injury. Taken together, our study discovered that CoQ10 can suppress NLRP3 activity in KCs and improves Foxp3 + Tregs differentiation depending on M2 macrophage polarization of KCs to ameliorate hepatic IRI. Graphical Abstract: ga1 Highlights: CoQ10 attenuated the hepatic ROS production and ischemia reperfusion injury. CoQ10 suppressed NLRP3 inflammasome activation and promoted Tregs infiltration. CoQ10 improved Foxp3 + Tregs differentiation depending on M2 macrophage polarization of KCs.